2006
DOI: 10.1136/bjo.2006.105577
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the contribution of CFH and chromosome 10q26 AMD susceptibility loci in a Russian population isolate

Abstract: Background/aims: A strong association has been confirmed between age-related macular degeneration (AMD) and variants at two independent loci including Tyr402His in the complement factor H (CFH) on 1q32 and Ser69Ala at LOC387715, a hypothetical gene on chromosome 10q26. The contribution of both loci to AMD was investigated in an isolated north-west Russian population. Methods: Together with a PLEKHA1 variant at 10q26, the CFH Tyr402His and LOC387715 Ser69Ala polymorphisms were genotyped in 155 patients with AMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 20 publications
1
14
1
2
Order By: Relevance
“…Moreover, assessment of differences between patients with GA and CNV has shown that the 270 T allele is primarily [28,29]. However, to our knowledge, the association of LOC387715 with the early stages of the disease has not been estimated in these or other studies.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, assessment of differences between patients with GA and CNV has shown that the 270 T allele is primarily [28,29]. However, to our knowledge, the association of LOC387715 with the early stages of the disease has not been estimated in these or other studies.…”
Section: Discussionmentioning
confidence: 82%
“…This association was reported in Northern Americans [17,25], and this was later confirmed in European [26,27,28,29] and Chinese populations [30]. In addition, genotype-phenotype correlation studies have suggested that the AMD-associated CFH genetic variant may also play a role in the type or size of neovascular lesions in exudative AMD and in response to treatment with anti-vascular endothelial growth factor (anti-VEGF) therapy such as bevacizumab [31].…”
Section: Introductionmentioning
confidence: 59%
“…The ORs for the Hong Kong population were similar to those of the Caucasian population. Studies have also found associations between the ARMS2 SNP and AMD in Russian [21], German [15] and Japanese populations [39].…”
Section: Plekha1/arms2/htra1mentioning
confidence: 96%
“…Specific associations have been identified in the populations of France, The Netherlands, Iceland, India, Germany, UK, China, Russia and Australia [12,[15][16][17][18][19][20][21][22]. The Y402H polymorphism does not appear to be an AMD risk factor in the Japanese population [23].…”
Section: Complement Factor Hmentioning
confidence: 99%